Modelling of crystallization process of polymeric composition in space and time - Borovik, Vitaly; Borovik, Vitaly (Eastern-European Journal of Enterprise Technologies, 2016)
In order to increase the efficiency of the analysis of the process of crystallization, by the example of a polymer composition the attempt of a multidimensional visualization was made, which allows creation of program systems to visually solve a wide range of tasks of the formation of crystals. The authors, based on the main provisions of the special theory of relativity, attached the physical sense to the concept of time, using the basic provisions of the concept of time and space that allows establishing a link between the various points of space. With the help of the quasi Lorentz transformation in the Minkowski universe, the modelling of the process of formation of crystals of polymer compositions was carried out in a four-dimensional space, combining physical three-dimensional space of factors affecting their formation, and time. The modeling of the process of crystallization in a 4D space has an important role not only as a great informative and probative force, but also as a means of promoting a better understanding of the processes of crystallization, in evaluating and searching for the optimal management of this process. The research results are likely to have a wide range of applications in the analysis of scientific, technical, technological and other processes, evolving in space and time.